Peningkatan Nilai Ekonomi Pada Kelompok Pembudidaya Udang Vaname (Litopenaeus vannamei) Laut Mina Budidaya Kabupaten Bireuen, Aceh - Yusrizal Akmal; Rindhira Humairani; M. Muliari; Ilham Zulfahmi (Jurnal SOLMA, 2021)
Background: Vaname shrimp farmers in Bireuen Regency have experienced a decrease in production because many pond farmers do not have adequate technology. To improve vaname shrimp output, the Laut Mina Budidaya Group has deployed closed system technology and water sanitation in reservoir ponds. The purpose of this service is to determine the rise in economic value of the vaname shrimp (Litopenaeus vannamei) Laut Mina Budidaya group in Bireuen Regency, Aceh. Methods: This service was carried out from August to November 2020. The service included direct assistance and practice in the areas of food management, water quality during shrimp rearing, shrimp health, and vaname shrimp harvesting, all of which were done using closed system technology. Results: Enlargement of vaname shrimp for 88 days with the number of fry of around 120,000 fish, the production results are 1,950 kg total weight. Meanwhile, the value of Feed Conversion Ratio (FCR) for partner ponds is 1.4 at harvest or if the average is 1.36. The FCR value is 1.4 which is considered good in the cultivation of vaname shrimp in partners so that the use of feed is classified as efficient. The profit earned is ± Rp. 23,834,000.00 and the value of the return on operational costs Revenue Cost Ratio (RCR> 1 category is feasible to work on). Conclusions: The maintenance of vaname shrimp by applying closed system technology can increase production and economic value in the maintenance of vaname shrimp in partner groups.